Activity match profile and physiological demands in female elite team handball - Michalsik Bojsen, L.; Madsen, K.; Aagaard, P. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The present study revealed that modern female elite Team Handball (TH) is a physically demanding intermittent team sport, where the players show substantial aerobic energy expenditure throughout the entire match and demonstrate only short periods of dominant anaerobic energy production. There were indications that temporary fatigue and a subsequent decline in performance may occur. Positional differences in physical demands were observed.